The nature, significance, and influence of perceived personal experience of climate change. (22nd July 2020) - Reser, Joseph P.; Bradley, Graham L.
Abstract: Following a previous 2014 review of perceived personal experience of climate change, the authors review relevant research published or reported between January 2014 and mid‐year 2019. The review findings suggest that the nature, significance, and influence of perceived personal experience of natural environment changes, conditions, and events deemed to be likely consequences of global climate change have been problematically conceptualized, researched, reported, and understood by many climate change scientists and by reporters of climate change science and their audiences. The nature, psychological significance, and psychological adaptation and issue engagement influence of personal experience of perceived environmental manifestations of climate change are arguably central considerations with respect to the human dimensions of climate change. These matters encompass public understanding of climate change science, both internal and external adaptation processes, and the psychological impacts of the ongoing stressor of climate change. They also affect issue engagement and behavioral change. It is increasingly necessary that existing issues with discipline‐based assumptive worlds, constructs and measures—and often unclear research and policy questions and objectives—be identified, clarified, and addressed. This particularly matters when researchers and policy makers are addressing public risk perceptions, understandings, and responses to global climate change, ideally to inform and enhance policies directed at climate change mitigation and adaptation, or, alternatively framed, directed towards public issue engagement and 'psychologically significant' as well as 'environmentally significant' behavioral change. This article is categorized under:  Perceptions, Behavior, and Communication of Climate Change > Perceptions of Climate Change